Factors Influencing Cryptocurrency Investment Decisions Among Indonesian Retail Investors: A Quantitative Study - Steven Purnama; Kamaruzzaman Onaning (UTSAHA: Journal of Entrepreneurship, 2026)
The rapid growth of cryptocurrency markets in Indonesia has attracted millions of retail investors, yet the behavioral and motivational factors that drive individual investment decisions in this context remain insufficiently understood. This study examines the simultaneous influence of five variables, namely investment experience, motivation, risk perception, investment interest, and financial literacy, on cryptocurrency investment decisions among Indonesian retail investors. A quantitative cross-sectional design was employed, with data collected from 168 respondents drawn from an active Indonesian cryptocurrency investment community forum through a structured Likert-scale questionnaire administered in February 2023. Multiple linear regression analysis was conducted using IBM SPSS version 23 to test six hypotheses. The results confirm that all five variables jointly and significantly influence cryptocurrency investment decisions, with the integrated model explaining 96 percent of the total variance in investment decisions. Among individual predictors, motivation emerged as the dominant positive influence, followed by risk perception and investment interest, while investment experience contributed a smaller but statistically significant positive effect. Financial literacy was the only variable to exert a significant negative effect, indicating that more financially literate investors exhibit greater caution toward cryptocurrency participation. These findings support, extend, and in the case of financial literacy partially contradict prior empirical studies, contributing an integrative multi-factor framework to the growing literature on cryptocurrency investment behavior in emerging markets. The study offers practical implications for investors, financial educators, and policymakers working to strengthen investor protection and financial decision-making quality within Indonesia's rapidly expanding digital asset ecosystem.